(untitled) (Herald of Journalism, 2026)
Cinema serves as a mirror of a nation’s spiritual life, revealing the peculiarities of national culture, history, traditions, and everyday existence. The history of Kazakh cinema dates back to the first half of the 20th century, evolving within the framework of Soviet cultural projects. The first Kazakh sound fea- Prominent examples of Kazakh cinematography include the works of Shaken Aimanov, such as The End of the Ataman and Angel in a Skullcap. Directors like Mazhit Begalin, Abdulla Karsakbayev, Oraz Abishev, and Satybaldy Narymbetov made significant contributions to the development of national cin-ema. Since independence, directors including Darezhan Omirbayev, Akan Satayev, Rustem Abdrashev, Ermek Tursunov, and Timur Bekmambetov have elevated Kazakh cinema to a global level. One of the central themes of modern cinema was the representation of the rich spiritual heritage and cultural iden-tity of the people. The films made contributed to the revival of the national spirit and patriotism. The purpose of the article is the scientific differentiation of trends in the promotion of national values in the media by synthesizing the discourse of Kazakh film production in the media. The documentary content of the study includes materials from national publications and el.kz, e-history.kz information sites such as Zhas Qazaq, Ana Tili, Alty Alash, Akzhunis-Astana, Zhas Alash, and Zhas Qazaq Uni. The article uses methods of comparative discourse analysis of research, content-typological clas-sification. The empirical approach has allowed the interpretation of ways of representing national values in digital and traditional media. Results indicate that key tools of media support for Kazakhstani cinema have been systematized, highlighting the importance of expert film criticism in forming cultural capital and strengthening Kazakh-stan’s international image. The scientific value of this article lies in its in-depth analysis of specialized media discourse and the identification of challenges within professional film journalism in the modern media system.